The Role of Management Accounting in Improving Program Effectiveness, Financial Accountability, and Resource Allocation in Namo Simpur Village Government - Ginting, Herminaria Br; Nasution, Yenni Samri Juliati; Nasution, Muhammad Syukri Albani (Akuntansi & Ekonomika, 2026)
This study aims to analyze the role of village management accounting in improving program effectiveness, financial accountability, and resource allocation in Namo Simpur Village. The research uses a quantitative causal associative approach. Data were collected through questionnaires from 31 village officials involved in financial management and program implementation. Data analysis involved applying classical assumption tests. simple linear regression, and partial significance tests. The results indicate that management accounting has a positive and significant role in supporting the effectiveness of program implementation, enhancing financial management accountability, and helping to allocate resources more effectively and efficiently. This study concludes that the implementation of management accounting is an important factor in improving the quality of village governance.